Interactive Triangular Global Model (ITGM) to Bridge Knowledge of Parents Towards Their Special Needs Children to Mitigate Communication Gap: Interactive Triangular Global Model to Bridge Knowledge of Parents - Asif Ali Syed; Hassan Ali Syed; Irfan M. Leghari; Anwar Ali Sanjrani; Sajid M (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2025)
This study discusses challenges faced by individuals, particularly the hard of hearing, in accessing education and employment due to societal stigmas and lack of support. Technology plays a crucial role in improving their quality of life. Parental knowledge and support are deemed vital, yet lacking, particularly in sign language understanding. The study uses a systematic literature review and proposes the ITGM model to address these issues. It highlights gaps in global sign language standards and grammar, suggesting training for parents and collaboration among educational institutions, NGOs, and policymakers. The aim is to enhance opportunities for the hard of hearing by fostering awareness and support, ultimately advocating for a global model in sign language development supported by adequate funding.